2013
DOI: 10.1144/sp379.14
|View full text |Cite
|
Sign up to set email alerts
|

Triassic pterosaurs

Abstract: Pterosaurs are a clade of highly specialized, volant archosauromorphs recorded from the Upper Triassic to the uppermost Cretaceous. Problematic remains referred to the Pterosauria are reported from the Triassic of Europe and both North and South America, but unequivocal pterosaur specimens are only known from the Alps (Italy, Austria and Switzerland: Preondactylus buffarinii, Austriadactylus cristatus, Peteinosaurus zambellii, Eudimorphodon ranzii, Carniadactylus rosenfeldi, Caviramus schesaplanensis and Raeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 109 publications
3
48
1
Order By: Relevance
“…These pterosaurs exhibit 0.6–1.5 m wingspans, disproportionately large heads and heterodont, monocuspid dentitions (Fig. A) (Wild, ; Wellnhofer, ; Dalla Vecchia, , ). They are largely interpreted as insectivorous and less frequently as piscivorous and carnivorous (Fig.…”
Section: Pterosaur Dietsmentioning
confidence: 99%
See 2 more Smart Citations
“…These pterosaurs exhibit 0.6–1.5 m wingspans, disproportionately large heads and heterodont, monocuspid dentitions (Fig. A) (Wild, ; Wellnhofer, ; Dalla Vecchia, , ). They are largely interpreted as insectivorous and less frequently as piscivorous and carnivorous (Fig.…”
Section: Pterosaur Dietsmentioning
confidence: 99%
“…). Rapid jaw closure, suggested by adductor muscle reconstructions, may have helped in the capture of small vertebrates (Ősi, ; Dalla Vecchia, ). Morphological reassessments of Dimorphodon forelimbs and pectoral girdle suggest an erect posture which would have facilitated terrestrial foraging for small vertebrates (Witton, ).…”
Section: Pterosaur Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. For a root flapping motion with no spanwise bending, the plunging motion is given by ht; y yγt Γy cosωt (1) where γ represents the section's dihedral (flapping) angle, Γ represents its amplitude, and ω is the flapping frequency. The dynamic twist is linearly proportional to the span according to the following relation:…”
Section: Wing Kinematicsmentioning
confidence: 99%
“…Their origin remained a mystery until, in 1801, George Cuvier discovered that the fossils belonged to a flying reptile. Katsufumi Sato, a Japanese scientist, did calculations using modern birds and concluded that it was impossible for a pterosaur to stay aloft [1]. Most of the many studies on pterosaurs describe the fossil remains, and discuss how a new specimen updates the current knowledge base.…”
mentioning
confidence: 99%